Prevalence of Cytomegalovirus among Women with Type 2 Diabetes and Estimation of Oxidative Stress Status and Levels of Some Interleukin in Kirkuk - Mohammed, Asmaa Jamal; Hussein, Afaf Saud; Shakor, Donia Suad (American Journal of Biology and Natural Sciences, 2025)
Introduction & aim: The human cytomegalovirus (HCMV) can cause cellular damage by triggering a series of inflammatory responses. Determining the levels of certain interleukins and oxidative stress indicators in women in Kirkuk City who had both type 2 diabetes and CMV was the goal of the current investigation. Materials & Methods: In this investigation, 190 patients with type 2 diabetes had serum samples taken in order to identify human cytomegalovirus antibodies. A control group of one hundred people without diabetes in various age ranges was also included. Samples were gathered between January and May of 2025. Using the enzyme-linked immunosorbent test technique, human cytomegalovirus antibodies were found in all of these serum samples. Patients with type 2 diabetes undergoing treatment at Kirkuk City, Iraq’s Special Center for Endocrine Glands and Diabetes were the study’s target population. Results: the results referred that the Cytomegalovirus infection was found in 167 (87.9%) of the 190 women with T2DM. It is found that the highest age group exposed to infection is 41-50 years, where the percentage reached 37.7%, while the age group 51-60 years is the lowest, if it reached 12.6%. There were no significant differences (P=0.185) between the age groups. Malondialdehyde (MDA) levels in serum of T2DM patients and T2DM & CMV demonstrated significant (P <0.05) elevated compared with control women. While, the levels of glutathione and catalase exhibited a significant (P <0.05) reduced in T2DM patients and T2DM & CMV compared with healthy women. For interleukins, IL-1beta and IL-17 in serum of T2DM patients and T2DM & CMV demonstrated significant (P <0.05) elevated compared with control women. Conclusions: The study concludes that there is a widespread prevalence of cytomegalovirus among women with type 2 diabetes, and that infection with the virus increases the risk of oxidative stress and raises the concentrations of interleukin in patients.